(untitled) (Mediscope, 2020)
Infection remains the main cause of morbidity and mortality in man, particularly in developing areas where it is associated with poverty and overcrowding. Infectious disease cause nearly 25% of all human deaths. This rate of mortality is increasing day by day due to antibiotic resistance, which is a major concern nowadays. Wound, respiratory tract and urinary tract are commonly associated with bacterial infection in both hospital and community settings. Area-specific monitoring studies aimed to gain knowledge about the type of bacterial pathogens responsible for these kinds of infections and resistance pattern of the causative agents may help clinicians to choose correct treatment regimen. So, the present study was aimed to investigate the pattern of bacteria which are responsible for Urinary tract, respiratory tract and wound infection. In addition, we also determined the antibiotic susceptibility profile of gram negative bacteria isolated from the patients who were attending both in and out patient departments at Sir Salimullah Medical College & Mitford Hospital (SSMC & MH) during January, 2009 to December, 2009. In this cross-sectional study, out of 308 clinical samples, a total of 159 (51.62%) samples were found to be positive for bacterial culture. Among the isolates 139 (87.42%) were Gram negative bacteria (Esch. coli, Klebsiella spp., Proteus spp., Pseudomonas spp., Acinetobacter spp.) and 20 (12.57%) were Gram positive bacteria (Staphylococcus aureus, Coagulase negative Staphylococcus). Antibiotic susceptibility of gram negative bacteria showed members of the Enterobacteriaceae were 100% sensitive to imipenem while they were found variably resistance to other commonly used antibiotics. We conclude that infections in the wound, respiratory and urinary tract are caused by both gram negative and gram positive bacteria. However, the frequency of gram negative bacteria is higher than the gram positive bacteria for these infections. Gram negative bacteria showed sensitive to imipenem and most of them were resistant to commonly used antibiotics. Therefore, clinicians should choose imipenem for patients who would be unresponsive to commonly used antibiotics. Mediscope Vol. 7, No. 1: Jan 2020, Page 17-24